2010
DOI: 10.1007/s10842-010-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Public Subsidies to Business: An International Comparison

Abstract: public support, business, subsidies, public procurement, effectiveness, H25, H57, L52,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…Yet, the authors also find substantially higher growth when subsidies target both incumbents and new market entrants and, in addition, incumbents are (heavily) taxed. Buigues and Sekkat (2011) summarize additional empirical evidence on the effect of subsidies on firm performance and conclude that most studies suggest a positive relation of public support on R&D. However, Buigues and Sekkat find that the effect of public support on productivity is inconclusive. In a related theoretical study Acemoglu et al (2006) show that low competition may have negative long-run effects and may prevent catch-up.…”
Section: Evidence and Theory On The Relation Between Industrial Policmentioning
confidence: 88%
See 1 more Smart Citation
“…Yet, the authors also find substantially higher growth when subsidies target both incumbents and new market entrants and, in addition, incumbents are (heavily) taxed. Buigues and Sekkat (2011) summarize additional empirical evidence on the effect of subsidies on firm performance and conclude that most studies suggest a positive relation of public support on R&D. However, Buigues and Sekkat find that the effect of public support on productivity is inconclusive. In a related theoretical study Acemoglu et al (2006) show that low competition may have negative long-run effects and may prevent catch-up.…”
Section: Evidence and Theory On The Relation Between Industrial Policmentioning
confidence: 88%
“…Second, 'hard' data on industrial policy lacks cross-country comparison because the definition and industrial policy measure are country (and industry) specific. For example, Buigues and Sekkat (2011) emphasize the difference in the measurement of subsidies across the OECD. Moreover, according to Livesey (2012) the framework of analysis of industrial policy in both developing and developed countries must be broad enough to capture the effect of (1) policies that target different industrial stages, (2) horizontal and vertical policy, (3) policy targeting firms of different sizes, and (4) policies for structural change and policies stimulating industrial upgrading.…”
Section: Industrial Policy Indicatorsmentioning
confidence: 99%
“…Different forms of publicprivate-partnerships have emerged, with the rationale for public involvement in the telecommunications sector being often geopolitical or strategic more than an economic one (Briglauer, Gugler, & Bohlin, 2013;Gómez-Barroso & Feijóo, 2010a). On a more general level, commentators like Buigues and Sekkat (2010) or Spector (2009), compare and contrast recent government approaches to state subsidies, industrial policies and other market interventions and found the share of GDP spent on public support is lower in the EU than in the US and argue for more research on specific public support policies.…”
Section: Market Liberalisation In the Telecommunications Sectormentioning
confidence: 99%
“…There is also evidence that higher spending translates into higher output as measured by patents or the number of innovative products introduced (Branstetter and Despite this evidence for effects of policy on location and R&D, evidence of effects on productivity is much weaker. Buigues and Sekkat (2011) survey the literature and find inconclusive results of policy on total factor productivity. Indeed, there is some evidence that less productive plants receive more subsidies so, to the extent that they expand their employment, measured aggregate productivity may be reduced (Criscuolo et al 2012).…”
Section: The Effects Of Policymentioning
confidence: 99%